An Interpretive Inquiry into Electoral Zoning Politics in Cross River State Before the 2023 Gubernatorial Elections - Essien, Essien Oku (International Journal of Humanities, Education, and Social Sciences, 2025)
This study evaluates the dynamics of electoral zoning in Nigeria in the context of the 2023 Cross River State gubernatorial election, analyzing how zoning politics intersect with public persuasion to shape electoral outcomes. Situated within a qualitative interpretivist paradigm, the research draws on in-depth interviews with key political actors and prospective voters. Guided by Agenda Setting and Social Judgment theories, the analysis examines the media’s influence in framing zoning debates and the electorate’s attitudinal responses to competing narratives. Findings reveal a nuanced relationship between historical zoning arrangements and shifting voter preferences, where loyalty to senatorial districts persists alongside an increasing demand for competence and visionary leadership beyond geographic identity. While zoning remains a strong determinant of political expectations, particularly benefiting the Southern Senatorial District, party ideology and candidate credibility emerge as equally decisive factors. The study also cautions against divisive ethnic rhetoric, emphasizing that failure to foster unity could threaten democratic stability in the state.